How to implement NIV in the ICU? - Arnal, Jean-Michel (Acta medica Lituanica, 2012)
NIV is widely used in the ICU for different types of respiratory failure. However, there is no recommendation on the method to implement successfully the NIV program in the ICU. The three keys are equipment, caregiver’s education and training, and organisation. Equipment should be considered purchasing the appropriate ventilators according to the number of patients and the type of patients admitted. Interface selection is very important and should not be neglected. Humidification devices should also be appropriate. Physician, nurses and respiratory therapist have to get education, practical training and a continuous training program. Organisation of NIV in the ICU is improved if there is a local developed protocol with precise indication criteria, initiation method, mask selection, ventilator settings, NIV session duration and monitoring.
Keywords: non-invasive ventilation; acute respiratory failure; mechanical ventilation